Effects of a rapid response team on patient outcomes: a systematic review - Zhang, Qiuxia; Lee, Khuan; Mansor, Zawiah; Ismail, Iskasymar; Guo, Yi; Xiao, Qiao; Lim, Poh Ying (Elsevier BV, 2024)
Background: Despite the widespread adoption of the rapid response team (RRT) by many hospitals, questions remain regarding their effectiveness in improving several aspects of patient outcomes, such as hospital mortality, cardiopulmonary arrests, unplanned intensive care unit (ICU) admissions, and length of stay (LOS). Objectives: To conduct a systematic review to understand the rapid response team's (RRT) effect on patient outcomes. Methods: A systematic search was conducted using PubMed, Cochrane, Embase, CINAHL, Web of Science, and two trial registers. The studies published up to May 6, 2022, from the inception date of the databases were included. Two researchers filtered the title, abstract and full text. The Version 2 of the Cochrane Risk of Bias tool and Bias in Non-Randomized Studies of Interventions (ROBINS-I) tool were used separately for randomized and non-randomized controlled trials for quality appraisal. Results: Sixty-one eligible studies were identified, four randomized controlled trials(RCTs), four non-randomized controlled trials, six interrupted time-series(ITS) design, and 47 pretest-posttest studies. A total of 52 studies reported hospital mortality, 51 studies reported cardiopulmonary arrests, 18 studies reported unplanned ICU admissions and ten studies reported LOS. Conclusion: This systematic review found the variation in context and the type of RRT interventions restricts direct comparisons. The evidence for improving several aspects of patient outcomes was inconsistent, with most studies demonstrating that RRT positively impacts patient outcomes.